National Investment Policy For The Implementation Of Asean Comprehensive Investment Agreement (ACIA) - Rubiyanto; Sri Purwaningsih; Sri Retno Widyorini (CV. Inara, 2022)
The 2009 ASEAN Comprehensive Investment Agreement (ACIA) itself is one of the elements in supporting the establishment of the ASEAN Economic Community in 2015. This ACIA applies to investments that have existed on the effective date of this Agreement and investments made after the entry into force of this Agreement. The implementation of the ASEAN Comprehensive Investment Agreement (ACIA) provisions requires that all ASEAN member countries ratify this instrument. Indonesia ratified ACIA through Presidential Regulation of the Republic of Indonesia Number 49 of 2011 concerning Ratification of the ASEAN Comprehensive Investment Agreement, so it must commit to wide open the door to liberalization in the investment sector based on the ASEAN Comprehensive Investment Agreement. The approach method used in this research is a normative juridical approach. The approach used in this research is a juridical analysis. The juridical analysis approach method is intended to study the meaning and purpose of various legal rules and regulations. The results of this study show that the ASEAN Comprehensive Investment Agreement is one of the important pillars in the effort to realize the ASEAN Economic Community, which aims to increase investment activities among ASEAN member countries and make the ASEAN region competitive so that it becomes one of the destinations for investors in the world. National investment policy in the context of implementing the ASEAN Comprehensive Investment Agreement is carried out by issuing Presidential Regulation of the Republic of Indonesia Number 49 of 2011 concerning Ratification of the ASEAN Comprehensive Investment Agreement.